Digital Emotion Contagion. Issue 4 (April 2020) - Goldenberg, Amit; Gross, James J.
Abstract : People spend considerable time on digital media, and are thus often exposed to expressions of emotion by other people. This exposure can lead their own emotion expressions becoming more similar to those of others, a process we refer to as 'digital emotion contagion'. This article reviews the growing literature on digital emotion contagion. After defining emotion contagion, we suggest that one unique feature of digital emotion contagion is that it is mediated by digital media platforms that are motivated to upregulate user emotions. We then turn to measurement, and consider the challenges of demonstrating that digital emotion contagion has occurred, and how these challenges have been addressed. Finally, we call for a greater focus on understanding when emotion contagion effects are likely to be strong versus weak or nonexistent. Highlights: People are spending increasing time on digital media, during which time they are exposed to the emotion expressions of others. This can lead their own emotion expressions becoming more similar to those of others. One distinction between digital and nondigital emotion contagion is that digital emotion contagion is mediated emotion contagion. The goals of digital media companies – to increase the frequency and intensity of user emotions – likely increase emotion contagion. Another distinction between digital and nondigital contagion is that the size and the character of digital networks may amplify contagion. However, increased exposure may also contribute to habituation and fatigue, which may serve as a counterweight, thus decreasing emotion contagion. Given that many factors contribute to changes in the emotion of a person from moment to moment, and the typical absence of information regarding user exposure to emotional content produced by others, it is challenging to determine when digital emotion contagion has occurred.